The detection of solid phosphorus and fluorine in the dust from the coma of comet 67P/Churyumov–Gerasimenko. Issue 2 (25th September 2020) - Gardner, Esko; Lehto, Harry J; Lehto, Kirsi; Fray, Nicolas; Bardyn, Anaïs; Lönnberg, Tuomas; Merouane, Sihane; Isnard, Robin; Cottin, Hervé; Hilchenbach, Martin; ,
ABSTRACT: Here, we report the detection of phosphorus and fluorine in solid particles collected from the inner coma of comet 67P/Churyumov–Gerasimenko measured with the COmetary Secondary Ion Mass Analyser (COSIMA) instrument on-board the Rosetta spacecraft, only a few kilometers away from the comet nucleus. We have detected phosphorus-containing minerals from the presented COSIMA mass spectra, and can rule out e.g. apatite minerals as the source of phosphorus. This result completes the detection of life-necessary CHNOPS-elements in solid cometary matter, indicating cometary delivery as a potential source of these elements to the young Earth. Fluorine was also detected with CF + secondary ions originating from the cometary dust.